Perspectives on the Use of Algae as Biological Indicators for Monitoring and Protecting Aquatic Environments, with Special Reference to Malaysian Freshwater Ecosystems - Wan Maznah Wan Omar (Tropical Life Sciences Research, 2010)
Algal communities possess many attributes as biological indicators of spatial and temporal environmental changes. Algal parameters, especially the community structural and functional variables that have been used in biological monitoring programs, are highlighted in this document. Biological indicators like algae have only recently been included in water quality assessments in some areas of Malaysia. The use of algal parameters in identifying various types of water degradation is essential and complementary to other environmental indicators. Komuniti alga mempunyai banyak sifat-sifat sebagai penunjuk biologi perubahan ruang dan masa alam sekitar. Parameter alga, terutamanya struktur komuniti dan variabel berfungsi yang dapat digunakan dalam program pemantauan biologi dibangkitkan dalam dokumen ini. Penunjuk biologi seperti alga hanya sejak kebelakangan ini dimasukkan ke dalam penilaian kualiti air di beberapa kawasan di Malaysia. Penggunaan parameter alga untuk mengenal pasti pelbagai bentuk pendegradan air adalah perlu dan pelengkap kepada penunjuk alam sekitar yang lain.